OPTIMASI PROSES PEMBEKUAN MINYAK KELAPA MURNI (VIRGIN COCONUT OIL) MENGGUNAKAN METODE RSM : KAJIAN SUHU DAN LAMA WAKTU PEMBEKUAN - Maimunah Hindun Pulungan; Oktavia Nur Fadhlillah; Ika Atsari Dewi (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2020)
This study aimed to determine the optimal temperature and duration of freezing during the freezing process of VCO. The experiment used optimization method of Response Surface Methodology (RSM) with 2 factors and 4 responses. The first factor was freezing temperature with temperature variations of -23, -28, and -33ÂºC. The second factor was the duration of freezing for 44, 48 and 52 hours. The response variables measured were refractive index, FFA, moisture content, and rendemen. These data were formulated by using Design Expert 7.5 Free Trial software. According to these factors and responses, 13 treatments were obtained. The best treatment results followed by organoleptic tests using the hedonic scale (color, aroma, and taste) carried out by 30 semi-trained panelists. Organoleptic data were analyzed by Friedman test (Î±=0.05). Based on the results of experiments that had been carried out, the right model for the response of refractive index, water content, and rendemen was quadratic, while the FFA response had linear model. The temperature factor significantly influenced the response of refractive index, FFA, moisture content, and rendemen. The freezing time factor did not significantly influence the response of refractive index, FFA, moisture content, and rendemen. The best treatment result was obtained at freezing temperatures of -32.474ÂºC for 48.081 hours. The best treatment produces 31.42% of rendemen, 1.45113 of refractive index, 0.12% of water content, and 0.058% of FFA. The assessment of respondents on VCO for color parameters and taste could be accepted by consumers, while aroma parameters could not be accepted by consumers. For the further research on products that had been made should be immediately conducted an organoleptic test, thus there was no change of aroma on VCO.